Sistem Pengering Biji Kakao dengan Menggunakan Metode Fuzzy Logic. - atmaja, ariyoga; sembiring, jaka persada (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2024)
Monitoring system The cocoa bean dryer is a system created to make it easier for emping melinjo craftsmen to combine the cocoa bean drying process based on temperature, humidity, weight and drying status. This system was created in the form of an application called MONIBIK Iot, in this application there is data on Temperature, Humidity, Weight and Drying Status as well as graphic displays. MONIBIK IoT can be accessed anywhere and at any time, provided the device must be connected to an internet connection. The conclusion from the research carried out is that the test results in the process of sending data from the system to the server display data values ​​in real time. Based on the test results of the sensor in measuring the level of drying of cocoa beans, based on temperature, humidity and weight results that can be obtained in the measurement process, the sensor can work well. The test data shows that the temperature value has increased, while the humidity and weight values ​​have decreased. This shows that the cocoa bean dryer is operating properly. Keywords— Monitoring, Mikrokontroler, Cocoa bean, Fuzzy.